2010
DOI: 10.1158/1535-7163.mct-09-0651
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Expression Signatures Predictive of Sensitivity to the Bcl-2 Family Member Inhibitor ABT-263 in Small Cell Lung Carcinoma and Leukemia/Lymphoma Cell Lines

Abstract: ABT-263 inhibits the antiapoptotic proteins Bcl-2, Bcl-x L , and Bcl-w and has single-agent efficacy in numerous small cell lung carcinoma (SCLC) and leukemia/lymphoma cell lines in vitro and in vivo. It is currently in clinical trials for treating patients with SCLC and various leukemia/lymphomas. Identification of predictive markers for response will benefit the clinical development of ABT-263. We identified the expression of Bcl-2 family genes that correlated best with sensitivity to ABT-263 in a panel of 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 47 publications
3
56
1
Order By: Relevance
“…Bcl‐xl and Bcl‐2 increased in HUVECs, IMR90 cells, and MEFs but not preadipocytes, suggesting that senescent HUVECs, IMR90 cells, and MEFs might depend more on this pro‐survival pathway than N‐resistant preadipocytes. Consistent with this, Bcl‐2 family molecular signatures, including Bcl‐xl, Bcl‐2, Noxa, and Bcl‐w, correctly predict susceptibility to N of 70% of small‐cell lung cancers and 81% of leukemias and lymphomas (Tahir et al ., 2010; Vo et al ., 2012). These same Bcl‐2 family molecular signatures are features of senescent HUVECs, IMR90 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl‐xl and Bcl‐2 increased in HUVECs, IMR90 cells, and MEFs but not preadipocytes, suggesting that senescent HUVECs, IMR90 cells, and MEFs might depend more on this pro‐survival pathway than N‐resistant preadipocytes. Consistent with this, Bcl‐2 family molecular signatures, including Bcl‐xl, Bcl‐2, Noxa, and Bcl‐w, correctly predict susceptibility to N of 70% of small‐cell lung cancers and 81% of leukemias and lymphomas (Tahir et al ., 2010; Vo et al ., 2012). These same Bcl‐2 family molecular signatures are features of senescent HUVECs, IMR90 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…N is senolytic in HUVECs, IMR90 cells, and MEFs, but not in senescent human primary preadipocytes. Based on these senescent cell type‐specific effects of N and its ability to treat cancers with specific Bcl‐2 family signatures (Tahir et al ., 2010; Vo et al ., 2012), we also tested signatures of Bcl‐2 family member proteins and found these signatures do indeed correlate with susceptibilities of different senescent cell types to N. This suggests that the molecular signatures of different types of senescent cells may be of utility in predicting responsiveness to Bcl‐2 family inhibitors or potentially to other classes of senolytic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Nontreated cells were used as a control. biomarker regardless of both the level of Bcl-2 (12)(13)(14) and the nature of the tumor cell. Indeed, several studies and ours have identified a uniform profile (Bcl-2 high /Mcl-1 low ) for ABT-737-sensitive cells.…”
Section: Discussionmentioning
confidence: 99%
“…The present investigation provides the biological rationale for these future clinical trials to evaluate ABT-737 alone or in combination with Mcl-1-reducing agents in MCL patients. Indeed, ABT-263 (navitoclax; Abbott), which is an orally bioavailable BH3-mimetic compound of the same class as ABT-737 and currently under investigation in hematologic and solid malignancies, could also be used as ABT-737 (13,(43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation